2009
DOI: 10.1007/s11695-009-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Insulin Sensitivity Before and After Bilio-pancreatic Diversion

Abstract: BPD increases the prevalence of subclinical or even frank hypothyroidism, without causing a defect in thyroid function itself, through several integrated mechanisms. (1) It induces iodine malabsorption, which is partially compensated by iodine excretion contraction. (2) The entero-hepatic open circulation determines fT3 loss, which induces subclinical or frank hypothyroidism in patients with pre-existing thyroid alterations, interfering also with the weight loss progress. Iodine supplementation should be recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is important to note that lean body mass is a better standard to gauge thyroxine requirements than weight. Rapid weight loss due to serious illness (e.g., certain malignancies, AIDS, malnutrition, and bariatric surgery) has also been associated with oral levothyroxine homeostasis [ 73 ]. Poor conversion of T4 to T3 It has been suggested that a genetic variation in deiodinase D2 (also called type 2 deiodinase, or 5′-deiodinase) may help to explain why some patients who fail to achieve control of hypothyroidism with a background of levothyroxine therapy respond to natural desiccated thyroid or to the combined therapy of levothyroxine and synthetic T3 [ 74 ].…”
Section: Primary Factors Contributing To Refractory Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that lean body mass is a better standard to gauge thyroxine requirements than weight. Rapid weight loss due to serious illness (e.g., certain malignancies, AIDS, malnutrition, and bariatric surgery) has also been associated with oral levothyroxine homeostasis [ 73 ]. Poor conversion of T4 to T3 It has been suggested that a genetic variation in deiodinase D2 (also called type 2 deiodinase, or 5′-deiodinase) may help to explain why some patients who fail to achieve control of hypothyroidism with a background of levothyroxine therapy respond to natural desiccated thyroid or to the combined therapy of levothyroxine and synthetic T3 [ 74 ].…”
Section: Primary Factors Contributing To Refractory Hypothyroidismmentioning
confidence: 99%
“…Rapid weight loss due to serious illness (e.g., certain malignancies, AIDS, malnutrition, and bariatric surgery) has also been associated with oral levothyroxine homeostasis [ 73 ].…”
Section: Primary Factors Contributing To Refractory Hypothyroidismmentioning
confidence: 99%
“…It has been reported that biliopancreatic diversion is associated with an increased prevalence of subclinical or even frank hypothyroidism through several integrated mechanisms including iodine malabsorption and increased free T3 losses through changes in the entero-hepatic circulation [92].…”
Section: The Thyroid and Bariatric Surgerymentioning
confidence: 99%
“…In contrast to gastric bypass or banding, it has been reported that biliopancreatic diversion is associated with an increased prevalence of subclinical or even frank hypothyroidism through several integrated mechanisms including iodine malabsorption and increased fT3 losses through changes in the entero‐hepatic circulation (24). While we do not have data on iodine status in our retrospective cohort study, we anticipate that patients were iodine‐replete as they were routinely prescribed the multivitamin and micronutrient supplement, Forceval® (Alliance Pharma plc., Wiltshire, UK) that provides 140 µg of iodine (100% of reference nutrient intake for adults in the UK (25)).…”
Section: Discussionmentioning
confidence: 99%